Assessment of knowledge, attitude and practice regarding dengue among undergraduates of Government Medical College, Western Maharashtra: a cross-sectional study - Bhadake, Kavita H.; Haralkar, Santosh J.; Roy, Payel (International Journal Of Community Medicine And Public Health, 2023)
Background: Dengue fever is one of the most important viral infections transmitted by Aedes mosquitoes and a major cause of morbidity and mortality globally. For its prevention and control need to assess knowledge, attitude and practice (KAP) level of individuals. Methods: This cross-sectional observational study was carried out in Dr. V. M. Government Medical College, Solapur after taking institutional ethical committee (IEC) approval during 01 October to 30 October in all 200 undergraduate students of a batch of MBBS was selected out of 3 batches by lottery method, who were given consent were included in the study, out of which 154 had responded to pre-tested, structured, questionnaire. Results: 78.57% participants had good knowledge regarding dengue fever causative agent, transmission, signs and symptoms, preventive and control measures. 92.2% participants had good attitude towards dengue fever seriousness, preventive and control measures, need of community participation, importance of immediate visit to health care facilities. All participants had good practices regarding dengue fever preventive and control measures and 98% participants had high KAP score >38 (out of 50) regarding dengue fever signs and symptoms, means of transmission and its preventive and control measures. Conclusions: Majority of participants had good knowledge regarding dengue fever causative agent, transmission, signs and symptoms, preventive and control measures. Majority of participants had good attitude towards dengue seriousness, preventive and control measures, need of community participation, and all participants had good practice regarding dengue fever preventive and control measures and majority of participants had high KAP score regarding the same.